Sensation and perception - Coastline Community College; Dallas County Community College District (Olathe, KS : RMI Media Productions, 1989)
Discuss the relationship between sensation and perception.
Director of photography, Ted Boehler ; editor, William Cartwright, Jr.
Narrator, Kate Porter
Keywords: Senses and sensation; Perception; Psychology